Betaine alleviates scleral remodeling in experimental myopia by regulating the TLR4/TAK1/NF-κB signaling pathway - Yinqiao Zhang; Yunxiao Xie; Zhaohui Yang; Runze Gao; Shuwen Yu; Jiawen Hao; Zhongyu Ma; Yuanting Yang; Ruixue Zhang; Hongsheng Bi; Dadong Guo (Toxicology and Applied Pharmacology, 2026)

Inverse-opal g-C3N4-supported halogen-regulated Bi2WO6/Bi2SiO5/BiOClxBr1-x heterostructures for simulated-sunlight-driven antibiotic degradation - Jingyue Hu; Yuanting Wu; Mato Knez; Lihui Guo; Cuicui Wang; Hulin Liu; Xinmeng Zhang; Ou Hai; Yunlong Xue (Journal of Environmental Chemical Engineering, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

The dietary flavonoid quercetin protects against visual cortical synaptic remodeling and ferroptosis in experimental myopia via the KEAP1-NRF2 pathway - Miao Zhang; Ruixue Zhang; Yuanting Yang; Xiaoyue Zhao; Baoyuan Sun; Zhongyu Ma; Mengke Wu; Jizhao Xin; Xuewei Yin; Hongsheng Bi; Dadong Guo (Food Bioscience, 2026)

Endoplasmic reticulum stress–based ATF6 signaling pathway: evaluation of 4-PBA improving retinal state in myopic guinea pigs - Mengke Wu; Miao Zhang; Mingbin Tian; Weibo Pan; Xuexin Wang; Ruixue Zhang; Yuanting Yang; Zhongyu Ma; Zhaohui Yang; Yinqiao Zhang; Hongsheng Bi; Dadong Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Construction of inhomogeneous bismuth-based heterojunctions with efficient interfacial charge transport: Bridging of BiOX - Yuanting Wu; Lihui Guo; Xuhua Liu; Xiaoying Wang; Jingyue Hu; Yunlong Xue; Ou Hai; Hulin Liu; Xinmeng Zhang; Weizhi Tian; Yongqiang Feng (Environmental Research, 2025)

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Construction of energy storage heterojunction and enhancement mechanism of dark and full-spectrum energy storage piezoelectric catalysis - Bixin Zhang; Guoqiang Tan; Wenlong Liu; Xiongtao Wu; Linxin Guo; Zeqiong Wang; Chunyan Zeng; Ying Liu; Tian Liu; Qian Yang; Ao Xia; Huijun Ren; et al. (Chemical Engineering Journal, 2025)

Transcriptome analysis of the genes and regulators involving in vitamin E biosynthesis in Elaeagnus mollis diels - Shuhui Du; Yuanting Guo; Qianqian Li; Xiaoyan Hu; Yang Tian; Baochang Cheng; Shengji Wang; Zhiling Wang; Ruifen Ren; Zhaoshan Wang (Plant Molecular Biology, 2024)

Roles of extracellular vesicles on macrophages in inflammatory bone diseases - Yifan Lin; Ziyan Wang; Shirong Liu; Jiaohong Liu; Zhiyi Zhang; Yuanting Ouyang; Zhikang Su; Ding Chen; Lvhua Guo; Tao Luo (Molecular and Cellular Biochemistry, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Prescribed-time observer-based sideslip compensation in USV line-of-sight guidance - Chunlai Yu; Junkang Zhu; Yuanting Hu; Hao Zhu; Ning Wang; Haohao Guo; Qinjin Zhang; Siyuan Liu (Ocean Engineering, 2024)

Asymmetric phosphorylation integrating host feature and blue thermally activated delayed fluorescence of thiaxanthene S,S-dioxide emitter for efficient heavily doped white organic light-emitting diodes - Yingying Chen; Chao Wang; Peng Ma; Yuanting Guo; Yuetong Liu; Aiqi Dang; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Thin and soft Ti3C2Tx MXene sponge structure for highly sensitive pressure sensor assisted by deep learning - Wang Guo; Zhiqiang Ma; Zhou Chen; Haojun Hua; Dong Wang; Mohamed Elhousseini Hilal; Yatian Fu; Pengyi Lu; Jian Lu; Yuanting Zhang; Derek Ho; Bee Luan Khoo (Chemical Engineering Journal, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

Techno-economic analysis of integrated carbon capture and utilisation compared with carbon capture and utilisation with syngas production - Yuanting Qiao; Weishan Liu; Ruonan Guo; Shuzhuang Sun; Shuming Zhang; Josh J. Bailey; Mengxiang Fang; Chunfei Wu (Fuel, 2023)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.